Efecto del programa educativo "Protar" para mejorar la producción de textos argumentativos en estudiantes del quinto grado de secundaria del colegio José Francisco Da Cruz, Villa Canaán 2021 - Santillan Ocmin, Víctor Fernando (2022)
The main purpose of the study was to evaluate the effect of the PROTAR educational program to improve the production of argumentative texts in students of the fifth grade of secondary school at José Francisco da Cruz School - Villa Canaán 2021. The research design belongs to the experimental type of study that was built from only one group, due to the existence of few students in the educational institution in the rural area, which was evaluated in two moments: pre-test and post-test with the same instrument. The sample of the population was selected in a convenient way, that is, the subjects that are available to the researcher, and was made up of 28 fifth grade secondary school students from José Francisco Da Cruz school, located in the rural town of Villa Canaán. To measure the production of argumentative texts, the written test technique was used, taking into account the indicators proposed in the variable. The Rubric was used as an instrument, which allowed obtaining information on the student's performance in a writing practice situation. The conclusión reached after being raised was the following "The application of the PROTAR program develops significant achievements in the production of argumentative texts in fifth grade secondary school students at the José Francisco da Cruz School - Villa Canaán 2022, being the average of the pretest 10.32, and the average obtained in the post test was 14.96.